Defamilisation and familisation measures: Can they reduce the adverse effects of pro-market pension reforms on women in Hong Kong and the UK?. (May 2016) - Chau, Ruby C.M.; Foster, Liam; Yu, Sam W.K.
This article explores the impact of defamilisation and familisation measures for women with caring responsibilities and their implications for access to pensions in later life in Hong Kong and the UK in the context of pro-market pension reforms. The first part of the article discusses pro-market pension reforms and their effects on women, the second discusses the potential role of defamilisation and familisation measures in reducing the adverse effects of pro-market pension reforms, and the third focuses on pension policies and examples of defamilisation and familisation measures in Hong Kong and the UK. Finally, on the basis of the discussion of the link between defamilisation and familisation measures and pension measures for women, we assert that both Hong Kong and the UK still have much to do in developing multi-option measures throughout the life course, measures that could limit future inequalities in retirement between men and women.